Development Of Infographic Teaching Materials On B.J. Habibie's Contributions to the Construction Of Barelang Bridge In Batam City To Enhance Historical Awareness And Learning Outcomes Of High School Students In Batam - Ariyani, Novi; Sri Andayani, Endang; Sayono, Joko (Yupa: Historical Studies Journal, 2024)
History learning is conducted with the aim of building and nurturing historical awareness of the importance of past events. Historical awareness holds a crucial position in the existence of a nation. History provides ample opportunities for students to actively analyze various discoveries. Observations conducted by researchers regarding the Indonesian history subject at SMAN 16 Batam revealed several facts: 1) textbooks, when viewed in terms of their physical appearance, generally appear dull, and 2) the topic of B.J. Habibie's contribution to the construction of Barelang Bridge in Batam has not been used in schools. This research aims to produce infographic teaching materials on B.J. Habibie's contribution to the construction of Barelang Bridge in Batam to enhance historical awareness and learning outcomes among high school students in Batam. This research adopts the ADDIE research model. The instruments used for data collection in this study include: (1) questionnaires, (2) observations, (3) interviews, and (4) documentation.